2016
DOI: 10.1021/acsnano.6b03939
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Evolution of Electrochemically Plated/Stripped Lithium Microstructures Investigated by Synchrotron X-ray Phase Contrast Tomography

Abstract: Due to its low redox potential and high theoretical specific capacity, Li metal has drawn worldwide research attention because of its potential use in next-generation battery technologies such as Li-S and Li-O2. Unfortunately, uncontrollable growth of Li microstructures (LmSs, e.g., dendrites, fibers) during electrochemical Li stripping/plating has prevented their practical commercialization. Despite various strategies proposed to mitigate LmS nucleation and/or block its growth, a fundamental understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
100
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 41 publications
8
100
0
Order By: Relevance
“…have confirmed the correlation between battery performance degradation and the dead Li dendrites by using electron paramagnetic resonance (EPR) spectroscopy . This correlation has been further substantiated by us via employing non‐destructive Synchrotron Radiation X‐ray Tomography (SRXT) technique . It is also important to emphasize that the morphological evolution of the accumulated dead Li structures and Li anode in LMBs during electrochemical cycling has also been fundamentally revealed by us via SRXT .…”
Section: Figuresupporting
confidence: 52%
“…have confirmed the correlation between battery performance degradation and the dead Li dendrites by using electron paramagnetic resonance (EPR) spectroscopy . This correlation has been further substantiated by us via employing non‐destructive Synchrotron Radiation X‐ray Tomography (SRXT) technique . It is also important to emphasize that the morphological evolution of the accumulated dead Li structures and Li anode in LMBs during electrochemical cycling has also been fundamentally revealed by us via SRXT .…”
Section: Figuresupporting
confidence: 52%
“…3D plus time) and even enabling quantitative information on 3D microstructural dynamics to be extracted. Recently, using synchrotron in-line phase contrast X-ray CT, Sun et al 28 non-destructively visualized the evolution of electrodeposited lithium, and observed separator cleavage caused by their growth. Here, we demonstrate the use of both synchrotron and laboratorybased X-ray micro-tomography to perform both in-situ and operando characterization and quantification of the morphological evolution that occurs at the surface of Li metal electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48] An electrochemical validation of the presently designed cell can be found in our previous reports. [49][50] SEM images of the surface and a cross-section of the employed trilayer Celgard ® 2325 separator are shown in Figure 2. From Figure 2a, the distinct slit-pore structure that results from extrusion and unidirectional stretching during the dry-process manufacture method is clearly observed.…”
mentioning
confidence: 99%